High pressure in-situ synthesis and physical properties of Cr3C2-Ni cermets. Issue 18 (15th December 2017) - Zhai, Wenyan; Gao, Yimin; Sun, Liang; Wang, Yiran; Niwa, Ken; Hasegawa, Masashi
Abstract: A novel Cr3 C2 -Ni cermets were successfully in-situ synthesized with Cr, C and Ni (20 wt%) mixed-powder at 1100 °C under 0–6 GPa isostatic pressure using a small-sized cubic-type multi-anvil press apparatus. High purity Cr3 C2 phase was generated in the cermets. Comparing with the conventional and reactive sintering, the sintering temperature and the average grain size of Cr3 C2 decreased by 200 °C and 50%, respectively. The physical properties, normalized lattice parameters and volumes of Cr3 C2 −20 wt%Ni cermet as a function of pressure had been studied both experimentally and by first-principles calculations for the first time.